S204. REDUCTION OF ANTIPSYCHOTIC DOSES AND POLYPHARMACY: TWO COCHRANE REVIEWS. (18th May 2020) - Leucht, Stefan; Samara, Myrto; Rodolico, Alessandro; Bauer, Ingrid; Bäckers, Lio; Bighelli, Irene
Abstract: Background: Antipsychotic drugs the only established monotherapy for the acute treatment and for the maintenance treatment of schizophrenia, but their downside are multiple side-effects which include weight gain, extrapyramidal side-effects and hormonal changes, some of can contribute to the documented on average 15 years shorter lifes of afflicted people. In addition, there are controversial data that suggest that antipsychotics could even lead to brain volume loss in a dose related fashion. In practice, acutely ill patients often receive high doses or combinations of antipsychotics. This is in part due to pressures such as suicidality, aggression, but also pressure from insurance companies and high rates of non-response, The question is, therefore, whether these high doses and polypharmacy can be carefully reduced during the maintenance phase. Of course, there is a difficult trade-off, because if the overall dose gets too low there is a risk for relapse. Methods: Two systematic Cochrane reviews, one on the reduction of antipsychotic doses, the other one on the reduction of antipsychotic polypharmacy in patients with schizophrenia, will be presented. For both reviews, the Cochrane Schizophrenia Group's register was searched for randomised controlled trials on thes questions. Open and blinded trials are accepted, but open trials are excluded in a sensitivity analysis. Patients need to be stable at baseline, doses and polypharmacy in the acute phase are not addressed. Any reduction of doses and any reduction of polypharmacy is accepted, irrespectively of which combinations or doses patients were originally on, which antipsychotics were taken off, how many antipsychotics were taken off/by how much doses were reduced and how fast the reduction was undertaken. The control groups are staying on polypharmacy/the original doses. The primary outcomes are quality of life and rehospitalisation. A high number of secondary outcomes such as symptoms, functioning, relapse and a broad range of side-effects are also addressed. The data are summarised in a random effects meta-analysis with standardised mean differences as effect sizes for continuous data and relative risks for dichotomous data. Heterogeneity is assessed with a chi-square test and the I-Square statistic. Publication is addressed with funnel-plots. Summary of findings tables are used to illustrate the results. Results: The search in the specialized register of the Cochrane Schizophrenia Group yielded 96 references, and 36 studies (32 + 4) that meet the inclusion criteria. The studies were published between 1963 and 2016 and they randomised between 13 and 374 participants. Without considering protocols and trial registrations, 9 were open RCTs, 5 were at least single blind and 13 were double blind. 16 studies were suitable for the meta-analysis of dose-reduction, 4 for the meta-analysis of the reduction of polypharmacy. Data extraction and analysis is currently ongoing. Preliminary findings will be presented at the meeting. Discussion: In the acute phase clinicians often use polypharmacy and high doses to treat schizophrenia. However, antipsychotics have many side-effects including a possibility to lead to brain volume loss in a dose-related fashion. The question whether such a polypharmacy and high doses can be reduced once patients are stable therefore currently one of the most burning ones. The Cochrane reviews will provide a comprehensive synthesis of the research that has been undertaken in this area.